Signifikansi Model Blended Learning Dalam Pembelajaran PAK di Lembaga Pendidikan - Koebanu, Dunosel Ir.; Adi Saingo, Yakobus (Sekolah Tinggi Teologi Immanuel Sintang Kal-Bar, 2024)
Learning activities should be carried out innovatively so that the material can be delivered well and students can understand it completely. Learning activities that are carried out innovatively can be implemented with a blended learning model, including Christian Religious Education learning which is able to collaborate offline and online learning approaches in schools as part of educational institutions. The aim of this research is to discuss the significance of the blended learning model in teaching Christian Religious Education in educational institutions. The method used is literature study by using scientific literature as a data collection tool. Any data that has been collected will be analyzed reductively through information filtering, organizing, and summarizing the discussion, so as to be able to explain the research results that the application of the blended learning model is very significant in the continuity of learning in educational institutions because it produces effective and efficient learning by combining face-to-face learning with online learning. The existence of the blended learning model is very significant because it helps students carry out Christian Religious Education learning activities in a fun way and increases students' enthusiasm and focus on learning in class. The blended learning pattern in the context of PAK learning which combines face to face and online learning can act as a forum for transferring and integrating religious values ??that support students' spiritual growth and form moral, ethical and social character in accordance with Biblical values.